2016
DOI: 10.1038/srep37285
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking the cell membrane: bio-inspired simultaneous functions with monovalent anion selectivity and antifouling properties of anion exchange membrane

Abstract: A new bio-inspired method was applied in this study to simultaneously improve the monovalent anion selectivity and antifouling properties of anion exchange membranes (AEMs). Three-layer architecture was developed by deposition of polydopamine (PDA) and electro-deposition of N-O-sulfonic acid benzyl chitosan (NSBC). The innermost and outermost layers were PDA with different deposition time. The middle layer was prepared by NSBC. Fourier transform infrared spectroscopy and scanning electron microscopy confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Actually, ion exchange membranes (IEM) as the key component of electrodialysis (ED) have been widely used to separate ions under electric field and to separate the monovalent anions/cations in coexistence with a large amount of multivalent ions . It has been revealed that cation exchange membranes (CEMs) modified by layer‐by‐layer assembly show extraordinary selectivity for multivalent/monovalent cations, because of electrostatic repulsion effect and mobility difference of cations .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, ion exchange membranes (IEM) as the key component of electrodialysis (ED) have been widely used to separate ions under electric field and to separate the monovalent anions/cations in coexistence with a large amount of multivalent ions . It has been revealed that cation exchange membranes (CEMs) modified by layer‐by‐layer assembly show extraordinary selectivity for multivalent/monovalent cations, because of electrostatic repulsion effect and mobility difference of cations .…”
mentioning
confidence: 99%
“…The current–voltage ( CV ) curve is another important variable to characterize the performance of electrochemical membranes. Usually, in a wide range of currents, it displays three different regions, which are Ohmic region, plateau region and over limiting region, respectively . Figure b shows the CV curves of GO, rGO, and rGO‐SDDS‐rGO#4.…”
mentioning
confidence: 99%
“…These organic substances stick easily to the membrane surface or cause blockages inside to membrane structure during separation (Fig. 5(c)) [180]. The mechanisms of organic fouling are related to the interaction between the organics and membrane surface such as electrostatic and hydrophobic interactions [181].…”
Section: Membrane Fouling Mechanisms In Mbrmentioning
confidence: 99%
“…8,9 The fouling extent of the membrane varies, depending on the structural properties of the membrane. 10,11 In this sense, the incorporation of ller materials in the membrane structure is an appropriate strategy to mitigate the fouling extent. Nano-size metal particulates with enhanced surface areas exhibit superb antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine has attracted much attention due to its strong adhesion and antifouling property on the surface of materials. 10,22 Based on the strong adhesion to solid material surfaces and intrinsic ability of easy secondary treatment of dopamine, a large number of methods have been proposed for the surface modication of solid materials. [23][24][25][26] In addition, due to the presence of amino and hydroxyl functional groups on dopamine, researchers used dopamine as an intermediate for further reaction; for example, Prokopios G. et al used the Michael addition reaction to successfully make dopamine derivatives.…”
Section: Introductionmentioning
confidence: 99%